Analisis Bibliometrik Penerapan Digital Marketing Dalam Pengembangan Bisnis UMKM - Anggreani, Irvana Ayu (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
The impact of rapid technological development makes digital marketing a way to support MSME business development. With a digital marketing strategi and choosing the right media, it will make it easier for MSMEs to reach the target market. This is inseparable from the role of digital marketing to introduce and market products from producers to consumers. In the modern era, social media users are increasing and reaching all levels of society. So that the use of digital internet technology and social media becomes more effective and efficient in developing MSME businesses. The method used in this study uses quantitative descriptive with a bibliometric approach and the help of VOSviewer software. The data source is taken from Google Scholar. Data collection techniques carried out in the form of secondary data. The number of metadata collected was 997 articles. The result of this study indicate that a number of writers are already interested in the theme of Implementing Digital Marketing in MSME Businenss Development in creasing from 2020 to 2021, to be precise at the time of the Covid-19 pandemic and can find out keywords that often appear and are related to each other as references for further research. Keywords: Business development; Digital marketing; MSME.